2016
DOI: 10.1111/jtsa.12225
|View full text |Cite
|
Sign up to set email alerts
|

Inference with the Whittle Likelihood: A Tractable Approach Using Estimating Functions

Abstract: The theoretical properties of the Whittle likelihood have been studied extensively for many different types of process. In applications however, the utility of the approach is limited by the fact that the asymptotic sampling distribution of the estimator typically depends on third‐order and fourth‐order properties of the process that may be difficult to obtain. In this article, we show how the methodology can be embedded in the standard framework of estimating functions, which allows the asymptotic distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Hence the quantity given in Equation (5) can be seen as a composite likelihood (Bevilacqua & Gaetan, 2015; Varin et al, 2011). We also observe that normal∇bold-italicθfalse(bold-italicθfalse)=0 such that our method fits within the general theory of estimating equations (Heyde, 1997; Jesus & Chandler, 2017).…”
Section: Methodssupporting
confidence: 67%
“…Hence the quantity given in Equation (5) can be seen as a composite likelihood (Bevilacqua & Gaetan, 2015; Varin et al, 2011). We also observe that normal∇bold-italicθfalse(bold-italicθfalse)=0 such that our method fits within the general theory of estimating equations (Heyde, 1997; Jesus & Chandler, 2017).…”
Section: Methodssupporting
confidence: 67%
“…The Whittle likelihood of Whittle (1953) is a frequency-domain approximation to the exact likelihood. This method is considered a standard method in parametric spectral analysis on account of its order n log n computational efficiency (Choudhuri et al, 2004;Fuentes, 2007;Matsuda & Yajima, 2009;Krafty & Collinge, 2013;Jesus & Chandler, 2017). However, it has been observed that the Whittle likelihood, despite its desirable asymptotic properties, may exhibit poor properties when applied to real-world, finite-length time series, particularly in terms of estimation bias (Dahlhaus, 1988;Velasco & Robinson, 2000;Contreras-Cristan et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The BND procedure and all three BFR( ) procedures estimate d well, regardless of the value of chosen or true value of the memory parameter. Because it is more challenging to estimate percentiles of Whittle likelihood estimators d d well (Robinson, 1978;Jesus and Chandler, 2017), we only consider the BND procedure to obtain adaptive estimates of d obtained by maximizing the Whittle likelihood. Figure 7 shows the average estimates of d obtained using the BND procedure, and indicates that BND procedure produces excellent estimates of d regardless of the true value of the memory parameter.…”
Section: Adaptive Point Estimation Of the Memory Parametermentioning
confidence: 99%